Staged dissection reduces blood loss in surgery for metopic synostosis - Anna Sundelin; Madiha Bhatti-Søfteland; Ingrid Stubelius; Tobias Hallén; Robert Olsson; Giovanni Maltese; Peter Tarnow; Karin Säljö; Lars Kölby (Journal of Plastic Surgery and Hand Surgery)
INTRODUCTION: Fronto-orbital remodelling for metopic synostosis is an extensive operation with substantial blood loss, particularly from emissary veins in the glabellar region. One possibility to reduce blood loss may be to stage dissection and cauterise anomalous emissary veins before dissecting in the subperiostal plane.